The economic and environmental effects of gold panning in a zone of armed conflict in the circle of Gao - Toure, Abdoulkadri Oumarou; Maiga, Fatoumata; N’diaye, Baba Faradji; Ouattara, Issa; Yalcouye, Bamoussa (International Journal of Environment, Agriculture and Biotechnology, 2023)
Since 2018, the Gao region has been the focus of a massive influx of people from all walks of life in search of the gold nugget that would make them rich. Indeed, gold has been discovered at various sites in the region, successively up to the present day. In a context of insecurity and occupation of the sites by armed groups, gold mining is carried out in an anarchic fashion with little regard for the environmental regulations in force. The aim of the study was to analyze the economic and environmental effects of gold panning in a context of armed conflict in the Gao circle, Mali. The methodology adopted consisted in conducting surveys among gold miners and local authorities in the region. Analysis of the survey results revealed that the positive impact was a drop in the unemployment rate among young people and an increase in their income above the minimum wage, according to 86% of respondents. However, the uncontrolled exploitation of sites using inappropriate machinery and techniques poses serious environmental problems, particularly for water, soil, flora and fauna resources. What's more, the waste generated is very poorly managed (59% of respondents dump it in the open air and 35.24% burn it). This has serious consequences for renewable natural resources. One of the main factors encouraging uncontrolled mining on gold panning sites is the failure of operators to comply with, or even ignore, current legislation in areas of insecurity. The Malian government must seek to secure these areas so as to ensure compliance with appropriate operating measures and better organize the industry. This will have the dual advantage of bolstering the coffers of the state and local authorities, as well as ensuring the safety of gold miners on the sites.